SCIENTIFIC METHODS IN TEACHING MATHEMATICS - Ishkurbanova Munavar Turayevna (Research Parks Publishing LLC, 2021)
The article is used to investigate the problem-solving abilities of primary school kids. The goal of this study is to see if students' mathematical problem-solving capabilities are improved by utilizing an article rather than a Mathematical Approach. The findings of this study revealed that pupils with strong mathematical problem-solving skills are more likely to succeed in school.